Experimental Investigation on Impact of EGR Configuration on Exhaust Emissions in Optimized PCCI-DI Diesel Engine - Getachew Alemayehu; Ramesh Babu Nallamothu; Deresse Firew; Rajendiran Gopal (Journal of Engineering)
The main objective of this work is to analyse the impact of different EGR configurations (no EGR, cold EGR, and hot EGR) on exhaust emissions of PCCI-DI engine. Methanol port injection, dieseline direct injection, advanced injection timing, and different EGR rates were adapted and optimized on the baseline engine. A hybrid algorithm of grey relational analysis with the Taguchi method was implemented for optimization. Results were compared among the PCCI-DI combustion strategy with the baseline using cold EGR, hot EGR, and no EGR configurations. Both cold and hot EGR configurations resulted in lower emission of NOx plus smoke at different loads. At low loads, hot EGR showed promising results of lower HC and CO than the cold EGR with a difference of 18.33% and 33.3%, respectively. NOx and smoke reductions simultaneously and better trade-offs were obtained using cold EGR configuration.